2020
DOI: 10.3390/nu12102934
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium Intake and Risk of Cardiovascular Disease: A Systematic Review and Dose-Response Meta-Analysis

Abstract: Dietary sodium intake has received considerable attention as a potential risk factor of cardiovascular disease. However, evidence on the dose-response association between dietary sodium intake and cardiovascular disease risk is unclear. Embase and PubMed were searched from their inception to 17 August 2020 and studies that examined the association between sodium intake and cardiovascular disease in adolescents were not included in this review. We conducted a meta-analysis to estimate the effect of high sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 84 publications
1
49
0
Order By: Relevance
“…The modifiable risk factors of CVD included unhealthy dietary habits, physical inactivity and smoking (3) . Previous studies found that high Na consumption was associated with CVD risk in both high-v.-low and dose-response meta-analyses (4) . The WHO recommends that dietary Na intake should be <2 g/d (5) .…”
mentioning
confidence: 94%
“…The modifiable risk factors of CVD included unhealthy dietary habits, physical inactivity and smoking (3) . Previous studies found that high Na consumption was associated with CVD risk in both high-v.-low and dose-response meta-analyses (4) . The WHO recommends that dietary Na intake should be <2 g/d (5) .…”
mentioning
confidence: 94%
“…In humans, an increase in potassium intake has been linked to decreasing blood pressure levels and stroke incidence, with an indication of a possible U-shape relationship with minimum risk at 3.5 g/day (i.e., 90 mmol/day) of potassium excretion [ 10 , 11 ]. Conversely, a decrease in sodium intake showed an approximately linear association with blood pressure levels [ 12 ], cardiovascular diseases [ 13 ], and stroke [ 14 ], with beneficial effects of sodium reduction in both subjects with and without hypertension [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 63) Herein, we will focus on 2 staple foods, fish and salt, that characterize the East Asian diet 64) and were previously suggested as risk factors for CVDs. 65) 66) On the other hand, consuming red meat, 67) 68) rice, 69) 70) and alcohol 71) 72) showed no or faint associations with the risk of CVDs among Korean and Japanese populations, and thus were not discussed in depth.…”
Section: Modifiable Cardiovascular Risk Factors In Korea and Japan In The Literaturementioning
confidence: 99%
“…Dietary sodium intake is a potential risk factor for CVD. 66) In a case-control study of 304 cases with stroke and 249 age-matched controls conducted in Korea, high sodium intake was associated with 40% and 50% higher odds of stroke in men and women, respectively. 76) Another case-control study from Korea (n=146) revealed that a substantially higher proportion of stroke cases (60.3%) preferred salty foods than their counterparts (20.5%).…”
Section: Modifiable Cardiovascular Risk Factors In Korea and Japan In The Literaturementioning
confidence: 99%